PBS / PGA composite material, biodegradable PBS / PGA composite film and preparation method thereof

By adding epoxy chain extender NC-514 to the PBS/PGA composite material, the problems of low barrier performance and phase separation of the PBS composite film are solved, and the PBS/PGA composite film with high toughness and high barrier performance are achieved, which is suitable for food packaging.

CN116285238BActive Publication Date: 2025-05-02CHINA SHENHUA COAL TO LIQUID & CHEM CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310005731.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-04
Publication Date
2025-05-02
Estimated Expiration
2043-01-04

AI Technical Summary

Technical Problem

The PBS composite film has low barrier properties for oxygen and water vapor, which cannot meet the needs of food packaging. At the same time, the compatibility of PBS and PGA is poor, resulting in phase separation problems.

Method used

PBS/PGA composite material is used and epoxy chain extender NC-514 is added to the blended resin. By improving the interface binding force of the two phases and the chain expansion capacity enhancement effect, the compatibility and barrier properties of the composite film are improved.

Benefits of technology

It improves the compatibility and barrier properties of the PBS/PGA composite film, enhances its mechanical properties, and can effectively block oxygen and water vapor, and is suitable for food packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116285238B_ABST
    Figure CN116285238B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of polymer material composite films, and in particular to a PBS / PGA composite material, a biodegradable PBS / PGA composite film and a preparation method thereof; the biodegradable PBS / PGA composite film is prepared by extrusion and blow molding of the PBS / PGA composite material, and the PBS / PGA composite material includes a blended resin and an epoxy chain extender added in an amount of 0-1.0 parts. The present invention can improve the compatibility of the blended material, and can prepare a PBS / PGA-based composite film with high toughness and high barrier properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material composite membranes, and in particular to a PBS / PGA composite material, a biodegradable PBS / PGA composite membrane and a preparation method thereof. Background Art

[0002] Due to the public's strong concern about environmental protection and potential energy crises, it has become a global trend to replace polymers synthesized from traditional petrochemical resources with polymers synthesized from biomass resources. As an emerging bio-based, biodegradable polymer, polybutylene succinate (PBS) has aroused great interest in many fields. PBS has good flexibility and can be used as a packaging material. However, the main problem limiting the expansion of PBS in the field of food packaging film is its low barrier properties to oxygen and water vapor, which cannot meet packaging needs.

[0003] Polyglycolic acid (PGA) is a green and environmentally friendly material that can be decomposed into glycolic acid in the environment. Glycolic acid is a natural metabolite that can be directly absorbed by mammalian cells. PGA has good mechanical strength and barrier properties. The barrier property of PGA to oxygen is 1000 times that of polylactic acid (PLA) and 100 times that of PET. By adding some PGA to PBS, the barrier property of PBS composite film can be effectively improved.

[0004] However, PBS and PGA have poor compatibility, and the addition of PGA will cause phase separation. In order to minimize the occurrence of phase separation, chain extenders are usually added to the blended material. The addition of chain extenders can improve the interfacial bonding strength of the two-phase blended material. In addition, biopolyesters are prone to hydrolysis and thermal degradation during melt processing due to the presence of ester groups. The addition of chain extenders can effectively solve the problem of reduced polyester molecular weight caused by hydrolysis and thermal degradation, and play a chain extension role. Since polyester contains terminal carboxyl groups and terminal hydroxyl groups, the functional groups contained in commonly used chain extenders include epoxy groups, isocyanates, oxazolines, etc. Epoxy compounds are often used due to their efficient chain extension effect.

[0005] In bio-polyesters (such as polylactic acid, polybutylene terephthalate-adipate-butylene adipate, etc.), the most commonly used epoxy chain extenders include BASF's ADR series and Shanxi Chemical Research Institute's KL-E series. Both ADR and KLE are obtained by copolymerization of styrene and glycidyl acrylate, both of which are derived from petroleum resources and are non-renewable.

[0006] In view of this, how to select a chain extender suitable for the PBS / PGA composite system to improve the performance of the composite material has become a topic worthy of study. Summary of the invention

[0007] The purpose of the present invention is to provide a PBS / PGA composite material, a biodegradable PBS / PGA composite film and a preparation method thereof, in view of the problems existing in the existing PBS / PGA composite system, which can improve the compatibility of the blended materials and prepare a PBS / PGA-based composite film with high toughness and high barrier properties.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] In a first aspect, a PBS / PGA composite material is provided, comprising a blended resin and an epoxy chain extender;

[0010] The blended resin includes PBS resin and PGA resin;

[0011] Based on 100 parts of the total weight of the blended resin, the added amount of the epoxy chain extender is 0-1.0 parts, for example, 0.01 parts, 0.04 parts, 0.1 parts, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, preferably 0.3 parts to 0.8 parts.

[0012] According to the PBS / PGA composite material provided by the present invention, in some embodiments, based on the total weight of the blended resin, the blended resin includes:

[0013] The percentage of PBS resin is 50wt%-90wt% (e.g., 55wt%, 60wt%, 65wt%, 70wt%, 80wt%, 85wt%),

[0014] The percentage of PGA resin is 10wt%-50wt% (for example, 15wt%, 20wt%, 30wt%, 40wt%, 45wt%).

[0015] In some embodiments, the epoxy chain extender is NC-514, and its chemical structure is shown in formula (I):

[0016]

[0017] In a second aspect, a biodegradable PBS / PGA composite membrane is provided, wherein the composite membrane is produced by processing the PBS / PGA composite material as described above.

[0018] According to the PBS / PGA composite membrane provided by the present invention, in some embodiments, the oxygen permeability of the PBS / PGA composite membrane is less than 240 cm 3 / (m 2 24h), for example, 200cm 3 / (m 2 24h), 150cm 3 / (m 224h), 100cm 3 / (m 2 24h)、50cm 3 / (m 2 24h), 20cm 3 / (m 2 ·24h).

[0019] The water vapor permeability of the PBS / PGA composite film is less than 140 g / (m 2 ·day), for example, 100g / (m 2 ·day)、50g / (m 2 ·day)、10g / (m 2 ·sky).

[0020] In a third aspect, a method for preparing the biodegradable PBS / PGA composite membrane as described above is provided, comprising the following steps:

[0021] The PBS / PGA composite material is added into an extruder for melt extrusion, and a composite material masterbatch is obtained through granulation; and then the obtained composite material masterbatch is blow-molded using a blow molding machine to prepare a biodegradable high-barrier PBS / PGA composite film.

[0022] In some embodiments, the extruder is a twin-screw extruder.

[0023] In some embodiments, the temperature in the extruder from the feed zone to the head zone is 200-215°C, for example, 205°C, 210°C.

[0024] Herein, a conventional blow molding device can be used to achieve blow molding. In some embodiments, the blow molding temperature is 170-190°C, for example, 180°C.

[0025] Cardanol is a versatile, renewable and cheap organic natural resource extracted from cashew nut shell liquid, which is an agricultural byproduct of the cashew industry and consists of a mixture of different long-chain phenols. Cardanol contains phenolic hydroxyl groups and double bonds in its structure, and cardanol oligomers containing diepoxy functional groups, such as cardanol epoxy resin NC-514, can be prepared through reaction. Blending an appropriate amount of PGA with PBS and using the diepoxy cardanol oligomer synthesized from bio-based monomers as a chain extender can effectively improve the compatibility of the blended materials and prepare a PBS / PGA-based composite film with both high toughness and high barrier properties.

[0026] The PBS / PGA biodegradable film disclosed by the present invention belongs to the field of biodegradable packaging film processing. Compared with other epoxy chain extenders, due to the smaller molecular weight of NC514, under the condition of the same mass addition amount, the molar number of NC514 is many times higher than that of other epoxy chain extenders, so the number of epoxy functional groups is also much higher than that of the latter two, and it has a higher reaction probability, so NC514 shows excellent chain extension and capacity expansion effect. The present invention mainly solves the problem of poor compatibility when using high barrier material PGA and PBS for blending, and has positive significance for broadening the application fields of PGA and PBS.

[0027] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0028] 1) Flexible biodegradable polyester PBS has excellent film-forming properties and ductility, but the barrier properties of PBS film are low. The composite material formed by adding high barrier biodegradable polyester PGA can solve the problem of poor barrier properties of PBS film;

[0029] 2) The use of NC514 epoxy chain extender can enhance the interfacial bonding force between the PBS / PGA phases and improve the chain extension and capacity expansion effect, thereby further improving the mechanical properties of the PBS / PGA composite film;

[0030] 3) The epoxy cardanol oligomer NC514 synthesized based on the biomass resource cardanol has excellent chain extension and capacity expansion effects on the PBS / PGA composite material, and can synergistically further improve the barrier properties of the composite film, such as the barrier properties of oxygen and water vapor. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of the blow molding process of Example 2;

[0032] Figure 2 (a) and Figure 2 (b) are cross-sectional and longitudinal SEM images of the composite membrane obtained in Comparative Example 1;

[0033] Figure 3 (a) and Figure 3 (b) are the cross-sectional and longitudinal SEM images of the composite membrane obtained in Example 3, respectively. DETAILED DESCRIPTION

[0034] In order to understand the technical features and contents of the present invention in detail, the preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described in the embodiments, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described here.

[0035] <Source of raw materials>

[0036] Chain extender NC514, from Cardolite,

[0037] ADR 4468, from BASF,

[0038] KLE 4370, from Shanxi Chemical Research Institute,

[0039] PBS, from Showa, Japan, brand number 1001MD,

[0040] PGA comes from Shanghai Pujing Chemical Technology Co., Ltd.

[0041] <Test Method>

[0042] Test of longitudinal tensile properties of samples: refer to GB / T 10004-2008 test;

[0043] Test of longitudinal tearing properties of samples: refer to GB / T 16578.1-2008 test;

[0044] Oxygen and water vapor transmission rate test of samples: refer to GB / T 1038-2000 and GB / T 1037-2021.

[0045] Example 1

[0046] 100 parts by weight of PBS / PGA blended resin (PBS accounts for 80wt%, PGA accounts for 20wt%) and 0.3 parts by weight of NC514 are mixed, added to a twin-screw extruder for melt extrusion, and granulated to obtain a composite masterbatch; the temperature of the extruder from the feeding zone to the head zone is 210-215°C.

[0047] Then, the obtained composite material masterbatch was blow-molded by using a blow molding machine, and the blow molding processing temperature was 170-190° C. to obtain a high-barrier PBS / PGA composite film; the product was labeled 80 / 20 / NC514-0.3.

[0048] Example 2

[0049] 100 parts by weight of PBS / PGA blended resin (PBS accounts for 80wt%, PGA accounts for 20wt%) and 0.5 parts by weight of NC514 are mixed, added to a twin-screw extruder for melt extrusion, and granulated to obtain a composite masterbatch; the temperature of the extruder from the feeding zone to the head zone is 210-215°C.

[0050] The obtained composite material masterbatch was then blow-molded using a blow molding machine, and the blow molding processing temperature was 170-190° C. to obtain a high-barrier PBS / PGA composite film, and the product was labeled 80 / 20 / NC514-0.5.

[0051] Example 3

[0052] 100 parts by weight of PBS / PGA blended resin (PBS accounts for 80wt%, PGA accounts for 20wt%) and 0.7 parts by weight of NC514 are mixed, added to a twin-screw extruder for melt extrusion, and granulated to obtain a composite material masterbatch; the temperature of the extruder from the feeding zone to the head zone is 210-215°C.

[0053] The obtained composite material masterbatch was then blow-molded using a blow molding machine, and the blow molding processing temperature was 170-190° C. to obtain a high-barrier PBS / PGA composite film, and the product was labeled 80 / 20 / NC514-0.7.

[0054] Example 4

[0055] 100 parts by weight of PBS / PGA blended resin (PBS accounts for 80wt%, PGA accounts for 20wt%) and 0.8 parts by weight of NC514 are mixed, added to a twin-screw extruder for melt extrusion, and granulated to obtain a composite masterbatch; the temperature of the extruder from the feeding zone to the head zone is 210-215°C.

[0056] The obtained composite material masterbatch was then blow-molded using a blow molding machine, and the blow molding processing temperature was 170-190° C. to obtain a high-barrier PBS / PGA composite film, and the product was labeled 80 / 20 / NC514-0.8.

[0057] Example 5

[0058] 100 parts by weight of PBS / PGA blended resin (PBS accounts for 70wt%, PGA accounts for 30wt%) and 0.7 parts by weight of NC514 are mixed, added to a twin-screw extruder for melt extrusion, and granulated to obtain a composite material masterbatch; the temperature of the extruder from the feeding zone to the head zone is 210-215°C.

[0059] The obtained composite material masterbatch was then blow-molded using a blow molding machine at a processing temperature of 180-190° C. to obtain a high-barrier PBS / PGA composite film, and the product was labeled 70 / 30 / NC514-0.7.

[0060] Example 6

[0061] 100 parts by weight of PBS / PGA blended resin (PBS accounts for 60wt%, PGA accounts for 40wt%) and 0.7 parts by weight of NC514 are mixed, and then added to a twin-screw extruder for melt extrusion granulation to obtain a composite masterbatch; the temperature of the extruder from the feeding zone to the head zone is 210-215°C.

[0062] The obtained composite material masterbatch was then blow-molded using a blow molding machine at a processing temperature of 180-190° C. to obtain a high-barrier PBS / PGA composite film, and the product was labeled 60 / 40 / NC514-0.7.

[0063] Example 7

[0064] 100 parts by weight of PBS / PGA blended resin (PBS accounts for 50wt%, PGA accounts for 50wt%) and 0.7 parts by weight of NC514 are mixed, added to a twin-screw extruder for melt extrusion, and granulated to obtain a composite masterbatch; the temperature of the extruder from the feeding zone to the head zone is 210-215°C.

[0065] The obtained composite material masterbatch was then blow-molded using a blow molding machine, and the blow molding processing temperature was 180-190° C. to obtain a high-barrier PBS / PGA composite film, and the product was labeled 50 / 50 / NC514-0.7.

[0066] Example 8

[0067] The preparation process of PBS / PGA composite membrane refers to Example 1, except that the addition amount of NC514 is 1.0 part by weight, and the product is marked as 80 / 20 / NC514-1.0.

[0068] Comparative Example 1

[0069] The preparation process of PBS / PGA composite membrane refers to Example 1, except that no chain extender is added, a blank control sample is used, and the product is marked as 80 / 20.

[0070] Comparative Example 2

[0071] The preparation process of PBS / PGA composite membrane was similar to that of Example 1, except that NC514 was replaced by ADR4468, and the product was labeled 80 / 20 / ADR4468-0.3.

[0072] Comparative Example 3

[0073] The preparation process of PBS / PGA composite membrane refers to Example 1, except that NC514 is replaced by ADR4468, and its addition amount is adjusted to 0.7 parts, and the product is marked as 80 / 20 / ADR4468-0.7.

[0074] Comparative Example 4

[0075] The preparation process of PBS / PGA composite membrane refers to Example 1, except that NC514 is replaced by KLE4370, which is recorded as 80 / 20 / KLE4370-0.3.

[0076] Comparative Example 5

[0077] The preparation process of PBS / PGA composite membrane refers to Example 1, except that NC514 is replaced by KLE4370, and its addition amount is adjusted to 0.7 parts, and the product is marked as 80 / 20 / KLE4370-0.7.

[0078] Table 1 Longitudinal tensile properties of the products obtained in each embodiment and comparative example

[0079]

[0080]

[0081] Table 2 Longitudinal tearing properties of the products obtained in each embodiment and comparative example

[0082]

[0083] Table 3 Oxygen and water vapor transmission rates of the products obtained in each embodiment and comparative example

[0084]

[0085]

[0086] As can be seen from Table 1 and Table 2, compared with the PBS / PGA composite film without adding chain extender in Comparative Example 1, in Examples 1 to 3, as the content of NC514 increases from 0.3 parts to 0.7 parts, the tensile strength, elongation at break, tensile modulus and tear strength of the composite film all increase significantly. As the content of NC514 continues to increase to 1.0 parts, the mechanical properties of the composite film obtained in Example 8 are slightly reduced, indicating that the content of NC514 is not as much as possible, and its dosage is a factor affecting the improvement of various properties of the composite film. If the chain extender is excessive, the excess NC514 fails to react with the terminal carboxyl groups of PBS and PGA, and cannot be dispersed in the composite material to play a plasticizing role, which will cause a decrease in tensile strength. Therefore, the optimal addition amount of NC514 is 0.7 parts.

[0087] In Comparative Examples 2 and 3, 0.3 parts and 0.7 parts of ADR4468 were added respectively, and in Comparative Examples 4 and 5, 0.3 parts and 0.7 parts of KLE4370 were added respectively. By comparison, it was found that, under the condition of the same amount of chain extender added, the elongation at break of the composite film with NC514 added was twice that of the composite film obtained by adding ADR4468 and KLE4370.

[0088] Figure 1 This is a diagram of the blow molding process of Example 2. It can be seen from the figure that the composite film bubble is stable and has uniform thickness.

[0089] The experimental results in the table show that the chain extender NC514 has excellent compatibilization properties for PBS / PGA composite films. The reasons are mainly attributed to two aspects: (1) Since the molecular weight of NC514 is relatively small (molecular weight is 508), while the molecular weights of ARD4468 and KLE4370 are about 6800-7250, when the added mass is the same, the molar number of NC514 is many times higher than that of the latter two, so the number of epoxy functional groups is also much higher than that of the latter two, and it has a higher reaction probability; (2) The epoxy functional groups of NC514 are located at both ends of the molecular chain, which has higher reactivity than the epoxy groups located in the branched structure of ARD4468 and KLE4370. Therefore, NC514 exhibits excellent chain extension and compatibilization effects in the composite film.

[0090] Figure 2 a and Figure 2 b are the cross-sectional and longitudinal SEM images of the composite membrane obtained by PBS / PGA / 80 / 20 without adding any chain extender. From the figure, it can be found that PGA and PBS have obvious phase interfaces. Figure 2 The white granular substance in b is PGA.

[0091] Figure 3 a and Figure 3 b are the cross-sectional and longitudinal SEM images of the composite film (80 / 20 / NC514-0.7) obtained in Example 3, respectively. It can be seen from the figure that after adding 0.7 parts of NC514, the interface between PGA and PBS phases is significantly reduced, and the cross-sectional and longitudinal surfaces become smooth, which illustrates the good toughening effect of NC514.

[0092] It can also be seen from Table 3 that due to the reduction of the phase interface, the composite film 80 / 20 / NC514-0.7 exhibits the lowest oxygen and water vapor permeability, has good barrier properties and excellent mechanical properties.

[0093] The composite film prepared by the present invention not only has excellent mechanical properties and oxygen and water vapor permeability, but also has biodegradability. The selected chain extender can be obtained from biomass source monomers, and has the characteristics of being green, environmentally friendly and non-toxic. In addition, the composite film is based on PBS, which has positive significance for solving the poor barrier properties of PBS film and broadening the application field of PBS.

[0094] The above describes some embodiments of the present invention, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A PBS / PGA composite material, characterized in that: including a blended resin and an epoxy chain extender; The blended resin includes PBS resin and PGA resin; Based on 100 parts of the total weight of the blended resin, the amount of the epoxy chain extender added is 0.1-1.0 parts; Based on the total weight of the blended resin, in the blended resin, The percentage of PBS resin is 50wt%-90wt%, The percentage content of PGA resin is 10wt%-50wt%; The epoxy chain extender is NC-514, and its chemical structure is shown in formula (I):

2. The PBS / PGA composite material according to claim 1, characterized in that: Based on 100 parts of the total weight of the blended resin, the added amount of the epoxy chain extender is 0.3-0.8 parts.

3. A biodegradable PBS / PGA composite membrane, characterized in that: The composite membrane is obtained by processing the PBS / PGA composite material as described in claim 1 or 2.

4. The PBS / PGA composite membrane according to claim 3, characterized in that: The oxygen permeability of the PBS / PGA composite film is less than 240 cm 3 / (m 2 ·24h).

5. The PBS / PGA composite membrane according to claim 3, characterized in that: The water vapor permeability of the PBS / PGA composite film is less than 140 g / (m 2 ·sky).

6. The method for preparing the biodegradable PBS / PGA composite membrane according to any one of claims 3 to 5, characterized in that: The steps include: The PBS / PGA composite material is added into an extruder for melt extrusion, and a composite material masterbatch is obtained through granulation; and then the obtained composite material masterbatch is blow-molded using a blow molding machine to prepare a biodegradable high-barrier PBS / PGA composite film.

7. The preparation method according to claim 6, characterized in that: The extruder is a twin-screw extruder.

8. The preparation method according to claim 6, characterized in that: The temperature in the extruder from the feed zone to the die zone is 200-215°C.

9. The preparation method according to claim 6, characterized in that: The temperature of the blow molding is 170-190°C.

Citation Information

Patent Citations

  • PGA-enhanced degradable film and preparation method thereof

    CN113388136A

  • Preparation of epoxy cardanol-based chain extender modified PBAT-PLA composite film

    CN115058103A